Exploring the Barriers, Opportunities, and Motivation for Agricultural Entrepreneurship of Rural Colombian Students Who Participated in Dual-Credit Programs - Carlos A. Parra; Neil Knobloch (Journal of International Agricultural and Extension Education, 2022)
Rural Colombian college students may be interested in pursuing entrepreneurship activities to improve their future and livelihoods. College students who participated in a dual-credit program as high school students completed a questionnaire to assess their motivations to participate in agricultural entrepreneurship activities and the barriers and opportunities to participate in rural entrepreneurship activities. We found that students were motivated to participate in entrepreneurship activities because of their motivations to be their own boss and job security. At the same time, the rural students perceived political and structural barriers as important to be addressed to develop entrepreneurship projects. Finally, participants agreed that personal opportunities related to education were essential for developing rural entrepreneurship activities. These results are important to develop policies and methodologies to improve students' preparation for their future and their communities.
Keywords: Colombia youth; rural; entrepreneurship; student motivation